Bending and breaking of stripes in a charge ordered manganite - Benjamin H. Savitzky (Nature Portfolio, 2017)
Charge-lattice coupling plays a central role in the exotic behaviors of multiferroic complex oxides, such as manganites, however, obtaining a microscopic picture is challenging. Here, Savitzky et al. map periodic lattice displacement fields at the picometer scale to study local order-disorder competition.